Penerapan Thematic Collaborative Learning Untuk Meningkatkan Keterampilan Berpikir Kritis Siswa SD - Ariyani, Yusinta Dwi; Wahyudi, Andi; Sejati, Rika Asmara (Universitas Muhammadiyah Magelang, 2022)
This study aims to determine the effect of thematic collaborative learning on critical thinking skills. This research is a quasi-experimental study with a pretest-posttest control group design. The research subjects were fourth grade students of Mangunan State Elementary School, Yogyakarta city. The sample was selected based on random sampling while the instrument used in this study was an Essay test to measure critical thinking skills. The data that has been collected is then analyzed using the t-test. The results showed that there are differences in critical thinking skills in thematic learning between students who learn to use collaborative learning and students who learn to use expository. Students who study using thematic collaborative learning have a higher level of critical thinking skills than students who learn using the expository learning model.